2022
DOI: 10.1186/s13054-022-04129-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of unrestricted visiting policy for critically ill patients: a meta-analysis

Abstract: Aim To compare the safety and effects of unrestricted visiting policies (UVPs) and restricted visiting policies (RVPs) in intensive care units (ICUs) with respect to outcomes related to delirium, infection, and mortality. Methods MEDLINE, Cochrane Library, Embase, Web of Science, CINAHL, CBMdisc, CNKI, Wanfang, and VIP database records generated from their inception to 22 January 2022 were searched. Randomized controlled trials and quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The importance of family input into the provision of ICU care is not new (20,21). Prior to the pandemic, research focused on the type of visitation arrangements ( exible vs xed) and demonstrated the impact on rates of delirium and ICU acquired infections (22). The present ndings extend this previous knowledge by delineating the impact that family visitation has on the entire ICU system, including care delivery and staff wellbeing.…”
Section: Discussionsupporting
confidence: 62%
“…The importance of family input into the provision of ICU care is not new (20,21). Prior to the pandemic, research focused on the type of visitation arrangements ( exible vs xed) and demonstrated the impact on rates of delirium and ICU acquired infections (22). The present ndings extend this previous knowledge by delineating the impact that family visitation has on the entire ICU system, including care delivery and staff wellbeing.…”
Section: Discussionsupporting
confidence: 62%
“…The importance of family input into the provision of ICU care is not new [ 21 , 22 ]. Prior to the pandemic, research focused on the type of visitation arrangements ( flexible vs fixed ) and demonstrated the impact on rates of delirium and ICU acquired infections [ 23 ]. The present findings extend this previous knowledge by delineating the impact that family visitation has on the entire ICU system, including care delivery and clinician well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Family, friends, and hospital volunteers can provide assistance with certain activities, such as reorientation, range-of-motion exercises, and oral fl uid encouragement; the feasibility and effectiveness of using volunteers for such a role has been well established. 20,24,25 During the COVID-19 pandemic, hospital visitation policies became increasingly restrictive, even to the point where loved ones were prevented from visiting patients who were actively dying. As we transition from a "pandemic approach" to a more "endemic approach" to COVID-19, hospitals are faced with liberalizing restrictive hospital visitation policies.…”
Section: Diagnosismentioning
confidence: 99%
“…Th e NP must ensure that physical restraints are ordered according to institutional policy. Since physical restraints do not [18][19][20]24,25,31 • Identify patients at high risk for delirium (that is, those with multiple predisposing factors), and implement prevention strategies early. *3,34 Haloperidol (Haldol)…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation